Big Book Media Development With See Think Wonder Approach to Increase Early Literacy of Early Childhood - Niasari, Armeta; Budiarti, Erna (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
This study aims to develop Big Book learning media with the See Think Wonder approach in improving early literacy of children aged 5-6 years. The method used is research and development (R&D) with the ADDIE model, which includes analysis, design, development, implementation, and evaluation. The results showed that the use of Big Book media can improve children's literacy skills, including vocabulary recognition, story comprehension, and communication skills. Children can make simple sentences from the vocabulary they hear and retell the content of the story in their own language, reflecting their understanding. Teacher observations show that the See Think Wonder approach is effective in increasing children's vocabulary, with each child adding three to five new words. In addition, the children also practiced their imagination and cognitive training through the questions asked, whether related to the story or not. Thus, this approach not only improves expressive language skills but also builds children's confidence in communicating. This study concludes that See Think Wonder-based Big Book media can significantly improve early literacy in young children, with an increase in vocabulary, the ability to make sentences, and the ability to ask questions. These results show the importance of using interesting and interactive media in early childhood education to support optimal literacy development